Корреляционные связи физиолого-биохимических показателей Populus deltoides Marsch. в условиях ртутного комбината - Коршиков, И.И.; Виноградова, Е.Н. (Промышленная ботаника, 2004)
In eastern cottonwood (Populus deltoides Marsch.) growing under conditions of mercury processing integrated works, high direct correlational connection has been revealed between mercury a umulation and TBA-active combinations in leaves. During the first part of plants vegetation period, 15 cases of significant correlational connections between the indices studied have been determined, and during the second vegetation part — 7 cases. The development of leaves lesions in the second part of vegetation is accompanied by destruction of interconnections conjugacy between their functional systems.